The effectiveness of imiquimod 5% cream as an anti‐wrinkle treatment: A pilot study - Altalhab, Saad (Journal of cosmetic dermatology, 2019)
Summary Background Imiquimod 5% cream is currently approved to treat several dermatologic conditions including actinic keratoses (AK), superficial basal cell carcinoma (sBCC), and genital warts. However, there are numerous studies published on the alternative off‐label uses of imiquimod cream. Photoaging of facial skin is an important use for topical skin treatments, yet few studies have evaluated the effect of imiquimod cream for this dermatological condition. Methods This was a prospective, noncomparative pilot study. We included 15 healthy subjects; out of them, 11 subjects completed the study. The subjects were instructed to apply imiquimod 5% cream to the periorbital area on three nonconsecutive days per week for eight consecutive weeks. Photographs were obtained at baseline and after 8 weeks of treatment. Improvement in overall periorbital skin appearance was assessed by an independent investigator who compared the baseline and post‐treatment clinical photographs. In addition, post‐treatment self‐assessment was completed by the subjects using a 5‐point Likert scale. Results Eleven of the 15 subjects completed the 8‐week regimen. Eight participants (72.7%) noticed at least a fair improvement in periorbital skin changes based on the self‐assessed 5‐point Likert scale. Quartile score was also assessed by the investigator which indicated that seven subjects (63.6%) had at least 26% improvement. Based on Fitzpatrick wrinkle‐scoring system, there was a significant reduction in the subjects' wrinkle severity following treatment (6.8 [mean] ± 1.7 [SD] vs 4.6 ± 2.5 [P < 0.005]). Conclusions Imiquimod 5% cream may be a safe alternative anti‐aging treatment. Larger scale studies are needed to confirm these results.